Multiple insights into the reproductive function of harbour porpoises (Phocoena phocoena): An ongoing study - Desportes, Geneviève; Kristensen, Jakob H; Benham, Deborah; Wilson, Sandie; Jepsen, Trine; Korsgaard, Bodil; Siebert, Ursula; Driver, Jörg; Amundin, Mats; Hansen, Kirstin; Shephard, Gwyneth (NAMMCO Scientific Publications, 2003)
The harbour porpoises kept at the Fjord & Bælt since April 1997 offer a unique opportunity to gain a better understanding of the reproductive function in harbour porpoises, especially in terms of physiological cycle and concomitant behavioural traits. A study was initiated in 1997 with the following aims: 1) characterising the annual reproductive cycle in terms of behaviour and endocrine activity; 2) finding the most suitable techniques for a longitudinal investigation of the reproductive function, in particular with respect of the small size of the species; 3) ensuring a precise monitoring of the reproductive state of the Fjord & Bælt porpoises; 4) evaluating the best techniques for a vertical assessment of the reproductive state in wild harbour porpoises; 5) providing comparative basis for toxicological studies. Three harbour porpoises have participated in the study: a male and a female estimated 1-2 years old at their arrival at the Centre in 1997, and a one-year old female. The different methods for investigating their reproductive function include techniques not previously used with harbour porpoises, such as behavioural observation, measurement of sexual hormones in blood and other matrices, vaginal cytology, body temperature, and ultrasound scanning of testes and ovaries. These methods are discussed in terms of practicality and invasiveness. Selected examples of the preliminary results obtained are reported. Projects have concentrated on the sexual behaviour of the adult male and female (frequency, initiative, courtship behaviours) and their hormonal correlates, as well as on the interaction of the juvenile with the 2 adult animals. Behavioural sexual activity is very seasonal (peaking at the end of July and August), as is the testosterone cycle (levels increasing from less than 1 ng/ml to 30 ng/ml in May) and the development of the testis (peaking in July-August). Progesterone and oestrogen levels vary between less than 1 to 17 ng/ml and less than 0.1 to 1.8 ng/ml respectively, but infrequent blood sampling precluded obtaining a detailed picture of the ovarian cycle. We are attempting to measure sexual hormones in saliva and eye secretion. Successful matings have been confirmed by the presence of sperm on vaginal smears in 4 consecutive summers, but no pregnancy has occurred yet.